KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP KELAS IX PADA MATERI BANGUN RUANG SISI DATAR DI KABUPATEN BANDUNG - Fitria Noviana; Sigit Mulqiyono; Muhammad Afrilianto (IKIP Siliwangi, 2018)
Students mastery of mathematical communication ability can be one of benchmark to know the level of students understanding about the material that has been submitted. Mathematics is not only a tool for thinking but also math can be a tool to communicate an idea. This research aim is to describe the mathematical communication ability of class IX SMP. The research takes place in one of SMP in Bandung Regency. The mathematics material that discussed is about polyhedron. Data were taken from the results of the test instrument about the ability of mathematics communication. The samples that researcher used are about 30 students of class IX SMP. The results of this research showed the percentage of students' mathematics communication ability at 31% that means most of the students have a low percentage of understanding mathematics communication.